Violência a tweets por hora: a violência de gênero sofrida por mulheres transexuais a partir do conflito entre liberdade de expressão e discurso de ódio no Twitter - VELOSO, Manoel Júnior Ferreira (2021)
This study is about the limit between freedom of expression and hate speech based on the observation of gender violence suffered by transgender women in cyberspace, through interactions on the social network Twitter. The analysis is based on virtual ethnography, where: i) reliability criteria for filtering informants within virtual communities were established; ii) the cultural entreé, with data collection based on silent observation of online social interactions; and iii) analysis of the collected material, with the categorization of data between "hate messages/speech" and "free expression messages", qualified according to the definitions presented in the theoretical framework and by the Platform's Policies and Rules of Use. In the end, it concludes that the permissiveness of the abuse of rights in the virtual environment, with the maintenance of online hate speech messages even in disregard of the Rules and Policies of Use of the social network.